A Mitochondria-Targeted Heptamethine Indocyanine Small Molecular Chelator for Attenuating Uranium Nephrotoxicity - Zaizhi Du; Xie Huang; Zifei Wu; Mingquan Gao; Rong Li; Shenglin Luo (MDPI AG, 2024)
Radionuclide uranium has both a chemical and radioactive toxicity, leading to severe nephrotoxicity as it predominantly deposits itself in the kidneys after entering into human bodies. It crosses renal cell membranes, accumulates in mitochondria and causes mitochondrial oxidative damage and dysfunction. In this study, a mitochondria-targeted heptamethine indocyanine small molecule chelator modified with gallic acid (IR-82) is synthesized for uranium detoxication. Both gallic acid and sulfonic acid, as two hydrophilic endings, make IR-82, being excreted feasibly through kidneys. Gallic acid with polyphenol groups has a steady metal chelation effect and potent antioxidant ability, which may facilitate IR-82-alleviated uranium nephrotoxicity simultaneously by enhancing uranium decorporation from the kidneys and reducing mitochondrial oxidative damage. Cell viability assays demonstrate that IR-82 can significantly improve the cell viability of uranium-exposed human renal (HK-2) cells. It is also demonstrated to accumulate in mitochondria and reduce mitochondrial ROS and total intracellular ROS, as well as intracellular uranium content. In vivo imaging experiments in mice show that IR-82 could be excreted out through kidneys. ICP-MS tests further reveal that IR-82 can efficiently decrease the uranium deposition in mouse kidneys. IR-82 treatment improves the animal survival rate and renal function of experimental mice after high-dose uranium exposure. Collectively, our study may evidence that the development of uranium decorporation agents with kidney-mitochondrion dual targeting abilities is a promising strategy for attenuating uranium-induced nephrotoxicity.